2016
DOI: 10.1037/mot0000040
|View full text |Cite
|
Sign up to set email alerts
|

People’s naiveté about how extrinsic rewards influence intrinsic motivation.

Abstract: Despite the voluminous empirical research on the harmful effects of extrinsic incentives (e.g., money, competition prizes, etc.) on people's intrinsic motivation ("undermining effect"), our society is still reliant upon the use of extrinsic incentives to motivate people. To better understand the reason underlying this theory-practice gap, the current study examined people's beliefs about how extrinsic incentives influence recipients' intrinsic motivation. Participants were presented with a description of a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 27 publications
(32 reference statements)
6
48
2
1
Order By: Relevance
“…6 It is important to note, however, that people generally overestimate the motivating power of extrinsic rewards and underestimate people's capacity to sustain task engagement. For example, Murayama et al (2017b) showed that people believe that extrinsic incentives are effective even in situations where the undermining effect is likely to happen. This tendency was observed even for participants who are currently in a position of teaching others.…”
Section: Implications For Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It is important to note, however, that people generally overestimate the motivating power of extrinsic rewards and underestimate people's capacity to sustain task engagement. For example, Murayama et al (2017b) showed that people believe that extrinsic incentives are effective even in situations where the undermining effect is likely to happen. This tendency was observed even for participants who are currently in a position of teaching others.…”
Section: Implications For Educationmentioning
confidence: 99%
“…Murayama et al (2018) also showed that people underestimate how much they can sustain task engagement for boring tasks. These studies indicate that our belief about motivation (known as metamotivation; see Miele and Scholer 2018;Murayama et al 2017b;Scholer et al in press) is often inaccurate. Such an inaccurate belief may lead schoolteachers to rely on extrinsic rewards more often than necessary in educational practice, hampering the potential development of interest.…”
Section: Implications For Educationmentioning
confidence: 99%
“…While the research reviewed above suggests that individuals can be quite sensitive to the trade-offs of qualitatively distinct motivational states, emerging research reveals that people also hold some inaccurate beliefs about motivation (Murayama et al, 2016; Murayama, Kuratomi, Johnsen, Kitagami, & Hatano, 2018; Scholer & Miele, 2016; Woolley & Fishbach, 2015). For instance, individuals appear to be overly pessimistic about their ability to sustain intrinsic motivation in the absence of extrinsic incentives (Murayama et al, 2018).…”
Section: Metamotivational Beliefs: When People Get It Right Versus Wrongmentioning
confidence: 99%
“…For instance, individuals appear to be overly pessimistic about their ability to sustain intrinsic motivation in the absence of extrinsic incentives (Murayama et al, 2018). Further, individuals fail to recognize that intrinsic motivation can actually be undermined by extrinsic incentives (Murayama et al, 2016) and fail to appreciate the value of intrinsic incentives when anticipating future tasks (Woolley & Fishbach, 2015). They also fail to appreciate the benefits of setting self-concordant (i.e., autonomous) goals to satisfy their needs (Werner & Milyavskaya, 2018).…”
Section: Metamotivational Beliefs: When People Get It Right Versus Wrongmentioning
confidence: 99%
See 1 more Smart Citation